Exaggerated activities of TRPM7 underlie bupivacaine‐induced neurotoxicity in the SH‐SY5Y cells preconditioned with high glucose. Issue 8 (31st May 2021) - Dai, Shuang‐Hua; Li, Ya‐Wen; Hong, Qing‐Xiong; Su, Tao; Xu, Shi‐Yuan
Abstract: Hyperglycemia is considered a risk factor for the enhancement of local anesthetic‐induced neurotoxicity. Transient receptor potential melastatin 7 (TRPM7), a kinase‐coupled cation channel, has been implicated in a variety of neuropathological processes, including intracellular calcium disturbance and high glucose‐induced neuropathy. In this study, we investigated whether TRPM7‐related pathophysiology is involved in bupivacaine‐induced neurotoxicity in SH‐SY5Y cells and how hyperglycemia acts as a risk factor. For initial neurotoxicity evaluation, it was confirmed that cell damage and apoptosis induced by acute exposure to bupivacaine were dependent on its concentration and glucose preconditioning. High glucose preconditioning facilitated the bupivacaine‐induced fast and temporary rise in intracellular free calcium concentration ([Ca 2+ ]i ), which was attributed to both calcium influx through TRPM7 and calcium store release. Additionally, bupivacaine was shown to increase TRPM7‐like currents, particularly in cells preconditioned with high glucose. Bupivacaine‐induced neurotoxicity in hyperglycemia was correlated with extracellular signal‐regulated kinase (ERK), but not protein kinase B (AKT) activation. Inhibition of TRPM7 and ERK activity alleviates bupivacaine neurotoxicity. These results suggest that therapeutically targeting TRPM7‐related pathophysiological changes could be a potential strategy for treating local anesthetic‐induced neurotoxicity exacerbated by hyperglycemia.